Ethically utilising COVID-19 host-genomic data - Christopher Gyngell; John Christodoulou; Julian Savulescu (npj Genomic Medicine, 2021)
Genetic variants that influence susceptibility to COVID-19 have recently been identified. In this manuscript, we identify and discuss some of the ethical and practical issues raised by these studies. We first outline the ethical case for providing COVID-19 susceptibility testing to healthcare workers, as well as highlighting risks associated with privacy and discrimination. We then argue that the existence of genetically susceptible individuals has implications for the ethical conduct of COVID-19 human challenge trials. Finally, we discuss the ethical issues that could arise from other COVID-19 host–genome interactions, including the prospect of personalized vaccines.